Hygrothermal behavior of energy diaphragm wall and the induced heat and moisture interaction with adjacent underground space - Xu Zhou; Xiaoling Cao; Ziyu Leng; Chao Zeng; Yanping Yuan; Shady Attia (Underground Space)
In the field of design and application of the energy diaphragm wall (EDW), plenty of research was focused on thermal performances and induced mechanical behaviors. The coupled heat and moisture transfer process and the induced impact on the adjacent underground space were lack of attention, which is inevitable due to the high humidity of the surroundings. Therefore, in this paper, a numerical model taking the gradient of the temperature and relative humidity as the driving potential was established to investigate the characteristics of the coupled heat and moisture transfer in the EDW. Firstly, the behavior of the coupled heat and moisture transfer in the summer and winter was investigated separately, and it was compared with the pure thermal model. Results show that the colder the wall surface, the more humid it is. The heat flux is enlarged by the operation of the EDW. Moreover, the heat flux will be underestimated by more than 3.43% in the heat extraction season and by more than 3.90% in the heat injection case if the moisture transfer is not considered. The following long-running investigations have revealed that the latent flux reaches its maximum and minimum value in transition seasons, with a value that is ten times smaller than that of the sensible heat flux. The sensible heat flux reaches 18.7 W/m2 in summer, while in winter it is −27.4 W/m2. The peak latent heat flux is reduced by 14.7% as a result of the combined effect of changes in surface temperature and humidity, due to the operation of the EDW. Additionally, the magnitude of these fluxes is affected by the indoor conditions (temperature and relative humidity of the indoor air) and the operating temperature of EDW. Therefore, an orthogonal test is performed to evaluate how much the discrepancies are induced by variations in those parameters. The impact of each parameter varies across the seasons (summer, transition season, and winter). However, the indoor relative humidity has a more significant influence on the water vapor flux in all the seasons. This paper provided details about the coupled heat and moisture transfer process in the EDW. Moreover, it attempts to raise an issue about the impact on the hygrothermal load induced by the heat and moisture flux through the wall surface when applying EDW in underground engineering.